Biodiesel production as a strategy for small producer (Research, Society and Development, 2022)
The trend of change in the energy matrix in relation to fuels, in the world, has led to the need for a series of researches, which seek to optimize the use of biodiesel and diesel-biodiesel blends of oilseeds, such as soybeans and other crops. This study aimed to demonstrate the production of biodiesel from crude soybean oil (cold extracted) from a mechanical press as a strategy for the small producer and to evaluate the performance of a generator engine, using the mixtures of this biodiesel and mineral diesel. Cold extracted soybean biodiesel blends (10, 20, 40%) and mineral diesel (90, 80, 60%) were used in a smaller and larger resistive load of approximately 4.6 kW and 1.6 kW respectively, applied to the generator engine in order to evaluate its performance. The biodiesel produced from soybean oil extracted from the mechanical press, presented the specifications in accordance with the ANP standards. The evaluation of the energy efficiency of the fuels, with the motor-generator set of the Branco brand, model BD 4000, showed variations in consumption, and the blend with 20% soybean biodiesel and 80% diesel showed a reduction in fuel consumption and a good set yield. The research results suggest this as a viable strategy for the small producer.